A Job Analysis for K-8 Principals in a Nationwide Charter School System - Laura Cumings; Chris L. S. Coryn (The Evaluation Center at Western Michigan University, 2009)
Background: Although no single technique on its own can predict job performance, a job analysis is a customary approach for identifying the relevant knowledge, skills, abilities, and other characteristics (KSAO) necessary to successfully complete the job tasks of a position. Once the position requirements are identified, the hiring process is faster and more effective because job candidates are evaluated on a common set of objective criteria. Purpose: The purpose of this study was to conduct a job analysis of the principal position for elementary and middle school public charter schools. Moreover, the final outcome of the job analysis was a linkage of KSAOs to their respective job tasks that could be used during the candidate selection process. Setting: The job analysis was conducted in a national K-8 charter school system. Subjects: The information collected during the job analysis came from six subject matter experts (SME) who were employed as a principal or as a supervisor of principals by the charter school system at the time of the study. The SMEs represented a balanced blend of perspectives of the principal position and they possessed a wealth of knowledge, job experience, and skill level that qualified them as experts of the principal position. Intervention: During the job analysis, SMEs provided information about the principal position. Research Design: The job analysis used a qualitative case study design with a convenience sample of SMEs. Data Collection and Analysis: Subject matter experts participated in three phases of data collection. The first two phases collected information on the essential job tasks and the third phase collected information on the KSAOs required to successfully complete the job tasks. Findings: In total, 314 essential job tasks were identified across 8 functional job categories. The job analysis condensed redundant job tasks and eliminated job tasks that were not endorsed by half of the SMEs, which totaled a final set of 84 essential job tasks. Then, SMEs rated the essential job tasks on several dimensions that were used to measure job task importance. Of the 84, 46 essential job tasks met the criterion of being the most important in terms of achieving organizational goals. A collaborative group that included the job analyst, principal recruiters and one SME identified the KSAOs necessary for completing the 46 essential job tasks. During the final phase of data collection, SMEs rated the KSAOs on the following dimensions: necessary for principal applicant to possess, practicality of finding a principal applicant with the KSAO, and consequence if KSAO is ignored in the selection process. Forty-nine of the 53 KSAOs met the inclusion criteria based on the ratings of the dimensions above. Conclusions: The results from the job analysis revealed the diverse set of KSAOs required to successfully complete the essential job tasks of the principal position. Thus, using objective criteria established from the job analysis is a critical step in selecting the candidate who is best suited to succeed in the principal position.